Sosialisasi Hukum Tentang Risiko dan Dampak Penyalahgunaan Serta Peredaran Narkotika bagi Generasi Muda di Nagori Rabuhit Kecamatan Gunung Maligas Kabupaten Simalungun - Ervina Sari Sipahutar; Roswani Siregar; Eka Umi Kalsum; Yunanda Eka Putra (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service Program aims to increase the understanding and legal awareness of the younger generation regarding the risks and impacts of drug abuse and distribution in Nagori Rabuhit, Gunung Maligas District, Simalungun Regency. The legal socialization activity was carried out through counseling methods, interactive discussions, and questions and answers involving youth, community leaders, and village officials as a preventive effort to reduce the number of drug abuse in the community. The material presented included the definition of narcotics, types and modes of distribution, medical, social, and psychological impacts, as well as the legal consequences for perpetrators of drug abuse and distribution based on applicable laws and regulations. The results of the activity showed an increase in participants' understanding of the dangers of narcotics and their legal implications, which was reflected in their active participation and ability to identify forms of drug abuse in their surroundings. This legal socialization is expected to shape critical attitudes and legal awareness of the younger generation, while encouraging community participation in sustainable drug prevention and eradication efforts in the Nagori Rabuhit area.